Patrones de comunicación acústica a lo largo de un gradiente de distribución geográfica en una especie de ave neotropical (2024)
The Cinnamon-rumped Woodpecker (Melanerpes rubricapillus) is a neotropical species whose vocal communication plays a key role in its ecology and behavior. However, its acoustic variability as a function of geographical, environmental, and social factors has been poorly studied, especially after its recent expansion in Colombia. This work analyzes how these factors influence its vocalizations, aiming to provide tools for its monitoring and conservation. Three objectives were proposed: 1. characterize vocalizations according to geographical distribution, 2. analyze the impact of environmental factors such as tree cover, and 3. explore acoustic overlap with other woodpecker species. Using 94 recordings from Xeno-canto, processed in Raven Pro 1.6, principal component analyses and multivariate statistical tests were applied. The results highlight that variables such as Center Frequency, Aggregate Entropy, and Bandwidth are determinant in acoustic differentiation. Although no clear patterns by latitude or longitude were observed, acoustic variations seem to be related to local factors such as environmental noise and social dynamics. Furthermore, acoustic overlap with other species was identified, evidencing the vocal flexibility of M. rubricapillus as an adaptive strategy. The study contributes to the knowledge of the species by showing how its vocalizations reflect adaptations to its environment, helping to understand acoustic communication patterns in neotropical birds. This reinforces the importance of vocalizations as practical tools for monitoring and conservation.